UJI KETAHANAN PREPARAT JARINGAN TUMBUHAN MENGGUNAKAN PEWARNA ALAMI BUAH NAGA (Hylocereus polyrhizus) dan KUNYIT (Curcuma domestica Val) DENGAN VARIASI WAKTU SEBAGAI SUMBER BELAJAR BIOLOGI DALAM BENTUK LKPD - Nisa Dewi Setyawati; Handoko Santoso; Anak Agung Oka (EDUBIOLOCK, 2024)
The aims of this study were 1) to determine the effect of time variation on preparation endurance, 2) to determine the best time variation on preparation endurance, 3) to determine whether LKPD (Student Activity Sheets) were appropriate as learning resources at school. This type of research is descriptive qualitative experimental research. This study used 4 treatments with 4 replications using a solution of dragon fruit (Hylocereus polyrhizus) and turmeric (Curcuma domestica Val) and 2 positive and negative controls. The positive control used a synthetic dye, namely safranin, and the negative control used no dye. Data analysis in this study was presented in the form of non-statistical qualitative descriptive analysis. Based on the results of the study, the durability of preparations for 0 days showed good tissue staining results, the durability of preparations for 2 days showed results of tissue staining that were still clearly visible, the durability of preparations for 3 days showed results of tissue staining that were no longer clear. The results of this study were declared "feasible" to be used as a medium for learning biology in class XI semester 1 senior high school for exploring cells.